A Trauma-Informed Approach to Sexual Violence Research Ethics and Open Science - Campbell, Rebecca; Goodman-Williams, Rachael; Javorka, McKenzie (Journal of interpersonal violence, 2019)
The practice of ethics in social science research is a reflexive process of self-review to define a profession’s collective responsibility in the face of changing norms and expectations. In recent years, we have seen transformative changes in how society thinks about supporting sexual assault survivors, and how the scientific community thinks about our obligations to society. Decades of research on trauma and its impact has raised awareness about the needs of victimized individuals, giving rise to the trauma-informed practice movement, which emphasizes that service providers must center survivors’ well-being in all interactions, decisions, and program practices. The field of sexual assault research helped give rise to this movement and provides empirical support for its guiding tenets, and in this article, we explore how to bring these ideas full circle to begin articulating trauma-informed principles for research. A trauma-informed perspective on research challenges scientists to go beyond the requirements of the Belmont Report (1979) and institutional review boards' (IRB) regulations to develop research procedures that fully support survivors’ choice, control, and empowerment. Such reflection on participants’ rights is particularly important given the open science movement sweeping academia, which calls on scientists to share their data publicly to promote transparency, replication, and new discoveries. Disseminating data could pose significant safety, privacy, and confidentiality risks for victims of sexual assault, so we need to evaluate what open science means within a trauma-informed framework. In this article, we examine three key stages of the research process—participant recruitment, data collection, and dissemination—and consider how trauma-informed principles could help, but also could complicate, research practices. We explore these tensions and offer potential solutions so that research on sexual trauma embodies trauma-informed practice.